Oral manifestations of secondary syphilis in the elderly - A timely reminder for dentists - Minicucci, Eliana Maria [UNESP]; Vieira, R. A. [UNESP]; Oliveira, D. T.; Marques, Silvio Alencar [UNESP] (Wiley, 2013)
Syphilis is a sexually transmitted infectious disease caused by Treponema pallidum. Cases of syphilis have increased in frequency and are challenging when affecting the elderly. The main causes of increased prevalence of syphilis are sexual promiscuity, lack of knowledge about the disease and decreasing use of barrier protection. Clinically, the oral manifestation of syphilis may resemble other entities, which hampers the correct diagnosis. We report a case of a 79-year-old male with weight loss and feeding difficulties. In the oral cavity there were ulcerative lesions in the hard palate and bilaterally in the buccal mucosa. The incisional biopsy revealed only a non-specific ulceration of the oral mucosa. After 20 days, the patient was re-evaluated and presented maculopapular lesions in the palmar and plantar areas. Positive serological venereal disease reference laboratory (VDRL) tests confirmed the diagnosis of secondary syphilis. The patient was treated with Benzathine penicillin G. After two weeks of treatment the oral lesion disappeared and the patient returned to normal feeding and gained weight. This case report reinforces the need to alert physicians and dentists to include sexually transmitted infections such as syphilis in the differential diagnosis of oral ulcerative lesions in elderly sexually active patients. © 2013 Australian Dental Association.
Keywords: elderly; Oral cavity; secondary syphilis